The Wampanoag Indians - Lund, Bill, 1954- (Mankato, Minn. : Bridgestone Books, 1998)
Provides an overview of the past and present lives of the Wampanoag Indians, covering their daily life, customs, relations with the government and others, and more.
Includes bibliographical references (p. 23-24) and index.
Keywords: Wampanoag Indians -- History -- Juvenile literature; Wampanoag Indians -- Social life and customs -- Juvenile literature; Wampanoag Indians; Indians of North America -- Massachusetts